Project Portfolio Selection Based on Risk Index - Navid Jamshidnejad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organizations, especially project-based ones, always face a set of project proposals to select from to meet their revenue targets. They maximize their profit from projects by evaluating the proposals and selecting the best for their portfolios. For this purpose, there are various criteria for considering different aspects of organizational goals. A criterion, which most models have failed to consider, is the project risk as well as the effect of project selection on the project portfolio risk. This becomes more important when it is realized that a major goal of creating organizational project portfolios is to mitigate the risks posed to organizations by the failure of single projects. This study proposes a project portfolio selection model based on the risk evaluation of project proposals by identifying the requirements of necessary processes for this purpose through a literature review and analysis of the developed models.